Social CRM framework for a telecomunication company in Malaysia - Abdul Rahman, Azra Ain (2014)
This research is regarding a Social CRM framework for a telecommunication company in Malaysia. This is because of the current trend where the organization is extending the communication channels by using social media such as Twitter and Facebook. The divisions in the organization are already using social media to communicate with the customer but unfortunately there is no framework to govern these initiatives. The information such as complaints, opinions, feedbacks and inquiries are not properly optimized since there is no collaboration between the divisions. There are few doubts about Social CRM and its implementation. The objective of the research is to propose a suitable Social CRM framework for a telecommunication organization. Then, to analyze the Social CRM case studies which are related to Social CRM framework as part of the process to construct the Social CRM framework for the telecommunication organization and also to validate the constructed framework. The study was conducted in a leading telecommunication organization in Malaysia. Quantitative method is chosen. Data were collected from survey and structured interview. The result of study shows that Social CRM has positive impact to the organization towards the satisfaction, trust and commitment of the customer. This can be a guideline to the organization that is planning to implement Social CRM.